Basic research in aeronautical science: opportunities for collaboration with the US Air Force - Maurice, Mark (2008)
The Air Forcé Office of Scientific Research (AFOSR) manages the basic research for the US Air Force. To maintain a world-class research portfolio, AFOSR looks worldwide to team with the best scientists and laboratories it can find. AFOSR has overseas detachments in London and Tokyo, and is opening a new office in South América. These offices conduct a number of programs that are designed to build relationships between AF funded US scientists and scientists abroad. These include visiting scientist programs; personnel exchanges; information exchanges; cooperative projects; cooperative conferences and workshops; and AF funded contracts and grants. This presentation will provide information about these programs for scientists interested in working with the US Air Forcé, and it will provide the current interests and directions of AF research in aeronautical science.